Small-sided games in handball: A narrative review - Clemente, F. M. (Strength and Conditioning Journal, 2025)
Small-sided games (SSGs) are widely used drill-based games that mimic the dynamics of a match while allowing coaches to tailor specific objectives, such as inducing physiological/physical stimulus or developing technical/tactical behaviors. Interestingly, by designing the SSGs with different modifications, player's responses can occur with a potential impact on the physical adaptations of players. With growing evidence about using SSGs in handball, there is now an opportunity to summarize the main acute effects induced by different task constraints. Furthermore, there is also an increasing body of evidence that can help coaches decide on the effectiveness of SSGs compared with other types of high-intensity interval training for improving physical fitness. Thus, this narrative review aims to summarize the evidence regarding using SSGs in handball, particularly regarding the acute physiological and locomotor demands, and physical fitness adaptations after exposing players to SSG-based programs.